Adherence to healthy dietary pattern is associated with lower risk of multiple sclerosis. (5th April 2022) - Keykhaei, Fatemeh; Norouzy, Somayeh; Froughipour, Mohsen; Nematy, Mohsen; Saeidi, Morteza; Jarahi, Lida; Amiri, Fatemeh; Malek Ahmadi, Mahsa; Norouzy, Abdolreza
Background: Different studies have confirmed the role of nutritional factors in the etiology of Multiple sclerosis (MS). However, dietary patterns associated with the risk of MS remain unknown. Objectives: This study aimed to investigate the possible relationship between the existing dietary patterns and the risk of MS. Methods: This case-control study was conducted in Mashhad city, Iran in 2015. In total, 197 MS patients and 200 control subjects (matched in terms of age, gender, education level, and body mass index) were enrolled in this study. The required data were collected through interviews and questionnaire completion. Moreover, the data on the usual dietary intake of each participant during the past year were evaluated using a valid and reliable semi-quantitative food frequency questionnaire (160 items). Logistic regression analysis was applied to discover the associations between dietary patterns and the risk of MS. Results: Four major dietary patterns were identified in this study, including Unhealthy, Western, Healthy, and Traditional. After adjustment for smoking habits, the family history of autoimmune diseases and the duration of breastfeeding, the highest tertile of Healthy dietary pattern was found to be associated with the reduced risk of MS by 74% (OR = .26; P < .001), whereas the Unhealthy dietary pattern was associated with a three-fold increased risk of MS (OR = 3.04; P < .001). However, no correlation was observed between the Western and Traditional dietary patterns and the risk of MS. Conclusion: According to the results of this study, a healthy diet may reduce the risk of MS, whereas an unhealthy dietary pattern may.